Productivity and quality of Bt cotton (Gossypium hirsutum) as influenced by planting geometry and nitrogen levels under irrigated and rainfed conditions - DADGALE, P R; CHAVAN, D A; GUDADE, B A; JADHAV, S G; DESHMUKH, V A; PAL, SURESH (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was carried out during two consecutive kharif seasons of 2009 and 2010 at research farm of Department of Agronomy, Marathwada Krishi Vidyapeeth, Parbhani to evaluate the effect of planting geometry and different nitrogen levels on productivity and quality of Bt-cotton (Gossypium hirsutum L.) under irrigated and rainfed conditions. The results reveals that, Bt cotton sown under irrigated condition (irrigation applied at three critical growth stages of cotton) significantly improved the seed cotton yield (33.71 q/ha) over rainfed condition (15.00 q/ ha). The growth attributes, yield contributing characters and ginning percentage were improved significantly in irrigation as compared to rainfed during both the seasons of experiment. The plant geometry of 120 cm × 45 cm recorded highest seed cotton yield (26.46 q/ha) and stood significantly superior over other planting geometries. It has 8.9 and 13.5% yield increment over 90 cm × 60 cm and 180 cm × 30 cm, respectively. All growth and yield contributing parameters were recorded significantly higher with 120 cm × 45 cm plant geometry as compared to other planting geometries, except plant height (cm), monopodials/plant, leaf area (dm2) and dry matter accumulation (g/plant). Application of nitrogen @ 150 kg N/ha to Bt cotton increases 25.5% and 8.6% seed cotton yield over 100 kg N/ha and 125 kg N/ha, respectively. Quality parameters did not influence significantly by irrigation, planting geometries and nitrogen levels confirms that fibre properties governs by genetic makeup and least affected by management practices.